2012
DOI: 10.1590/s1677-55382012000300015
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratorial study of HPV infection in men infected with HIV

Abstract: ARTIcLe InfO _______________________________________________________________ _____________________

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
4
0
2
Order By: Relevance
“…Thus, several studies have found an increased prevalence of HPV in individuals who are also HIV-infected17. Likewise, HIV infection can influence the natural history of HPV, by increasing the likelihood of a persistent infection and achieving greater virulence15.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, several studies have found an increased prevalence of HPV in individuals who are also HIV-infected17. Likewise, HIV infection can influence the natural history of HPV, by increasing the likelihood of a persistent infection and achieving greater virulence15.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, Figliuolo et al . [ 15 ] observed high rates of HPV in HIV positive male heterosexual population, probably due to the high rate of female infection in our population, demonstrated in study done by Côrrea et al . [ 16 ] conducted in Manaus, State of Amazonas, Brazil.…”
Section: Discussionmentioning
confidence: 52%
“…In women with immunodeficiency, iatrogenic or acquired, the prevalence of HPV-associated lesions is higher than in immunocompetent individuals [9] . HIV-seropositive subjects experience an increased infection rate with a high number of relapse after treatment and an accelerated development of HPV-associated cancer [10] , [11] . In HIV-infected men, the prevalence of HPV in the genital area is 18.2% while that in the anus is 59.3% [12] , [13] .…”
Section: Introductionmentioning
confidence: 99%